2015
DOI: 10.1007/s00401-015-1413-4
|View full text |Cite
|
Sign up to set email alerts
|

Templated misfolding of Tau by prion-like seeding along neuronal connections impairs neuronal network function and associated behavioral outcomes in Tau transgenic mice

Abstract: Prion-like seeding and propagation of Tau-pathology have been demonstrated experimentally and may underlie the stereotyped progression of neurodegenerative Tauopathies. However, the involvement of templated misfolding of Tau in neuronal network dysfunction and behavioral outcomes remains to be explored in detail. Here we analyzed the repercussions of prion-like spreading of Tau-pathology via neuronal connections on neuronal network function in TauP301S transgenic mice. Spontaneous and GABAAR-antagonist-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
153
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(163 citation statements)
references
References 76 publications
10
153
0
Order By: Relevance
“…In vivo studies of prion-like induction of tauopathy have utilized intracerebral injection of brain lysate from tau transgenic mice or human tauopathy into P301L or P301S human tau transgenic mouse models (61-63), as well as the ALZ17 WT human tau mouse line, which has been reported to show inclusions following brain lysate from tauopathy mice or human cases, but this is a slower process (32,33). Studies using recombinant fibrillar tau for direct intracerebral seeding demonstrated the induction of tau pathology in transgenic mice expressing either P301L or P301S human tau, but not in transgenic mice expressing WT human tau (34,35,64,65). However, it is likely that tau aggregates within brain lysate have higher seeding potencies than recombinant tau fibrils (54).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies of prion-like induction of tauopathy have utilized intracerebral injection of brain lysate from tau transgenic mice or human tauopathy into P301L or P301S human tau transgenic mouse models (61-63), as well as the ALZ17 WT human tau mouse line, which has been reported to show inclusions following brain lysate from tauopathy mice or human cases, but this is a slower process (32,33). Studies using recombinant fibrillar tau for direct intracerebral seeding demonstrated the induction of tau pathology in transgenic mice expressing either P301L or P301S human tau, but not in transgenic mice expressing WT human tau (34,35,64,65). However, it is likely that tau aggregates within brain lysate have higher seeding potencies than recombinant tau fibrils (54).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous mouse studies have demonstrated that tau aggregates inoculated into the brain trigger spreading tau pathology [2, 12, 13, 23, 25, 27, 31, 36]. Further, we previously observed a steady increase in tau seeding activity in the PS19 tauopathy mouse brain, even in the absence of seed inoculation [21, 39].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, recent studies have shown that propagation and seeding of Aβ, tau, and α-syn in a prion-like manner might also contribute to neurodegeneration [22][23][24][25][26][27][28]. Remarkably, there is also evidence that these various protein aggregates can interact with each other [29].…”
Section: Introductionmentioning
confidence: 99%